A clean road to international trade: Environmental regulations and the cleanliness of export enterprises - Weijian Du; Yuhuan Fan; Mengjie Li (Heliyon, 2023)
This study explores the impact of environmental regulations on the clean product exports of firms and the mechanism of this impact from the dual perspectives of the extensive and intensive margins. It uses matched micro data and aims to explore the clean road to international trade. According to the benchmark regression, environmental regulations improve the export intensity of clean products. However, their impact on the export probability of clean products is not significant. That is, environmental regulations promote the intensive margin of enterprise clean product exports but do not promote the extensive margin of enterprise clean product exports. The mechanism analysis shows that the cost effect is an important way for environmental regulations to promote the cleanliness of export products. However, the channel of technological innovation is not verified. In addition, compared with command-and-control and voluntary public policy tools, market-inspired environmental regulations have a stronger promoting effect on the cleanliness of export enterprises. This study provides microevidence and a policy basis for improving the environmental policy system and for the sustainable development of international trade.